Coiled-coil domain containing protein 124 is a novel centrosome and midbody protein that interacts with the Ras-guanine nucleotide exchange factor 1B and is involved in cytokinesis. - Pelin Telkoparan (Public Library of Science (PLoS), 2013)
Cytokinetic abscission is the cellular process leading to physical separation of two postmitotic sister cells by severing the intercellular bridge. The most noticeable structural component of the intercellular bridge is a transient organelle termed as midbody, localized at a central region marking the site of abscission. Despite its major role in completion of cytokinesis, our understanding of spatiotemporal regulation of midbody assembly is limited. Here, we report the first characterization of coiled-coil domain-containing protein-124 (Ccdc124), a eukaryotic protein conserved from fungi-to-man, which we identified as a novel centrosomal and midbody protein. Knockdown of Ccdc124 in human HeLa cells leads to accumulation of enlarged and multinucleated cells; however, centrosome maturation was not affected. We found that Ccdc124 interacts with the Ras-guanine nucleotide exchange factor 1B (RasGEF1B), establishing a functional link between cytokinesis and activation of localized Rap2 signaling at the midbody. Our data indicate that Ccdc124 is a novel factor operating both for proper progression of late cytokinetic stages in eukaryotes, and for establishment of Rap2 signaling dependent cellular functions proximal to the abscission site.